Finance of International Trade (Kwara, Ilorin: Oak Professional Publishing Ltd, 1991)
This study text has been localized and designed to cover the Chartered Institute of Bankers of Nigeria's Syllabus of the Finance of International Trade.
First edition, September 1990. First localized edition September 1991.
Includes index
osc 27/7/16
Loans
Keywords: International Trade; Finance